Synthesis and Characterization of Some Hexaphenyldilead Complexes with Bifunctional Tridentate Schiff Bases - JAIN, POOJA; JAIN, BHAWANA; SINGH, SANDHYA; PATHAK, VISHAL; PATHAK, PRABHAT (Asian Journal of Chemistry, 2010)
The reactions of hexaphenyldilead with bifunctional tridentate Schiff bases in 1:2 molar ratios have been studied in anhydrous benzene. All the reactions were found to be quite facile and lead-lead bond was cleaved in preference to the lead-carbon bond. The resulting derivatives were yellow solids. They are quite stable in air and are not easily attacked by moisture. They are soluble in DMF and DMSO only. The lead atom, in these complexes, has a coordination number of six.